2021
DOI: 10.1248/bpb.b21-00071
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Oridonin in a Mouse Model of Acute Kidney Injury <i>via</i> Suppression of Macrophage Involved Inflammation

Abstract: Ischemia-reperfusion injury (IRI) is the major cause of acute kidney injury (AKI). The previous studies demonstrated thatOridonin can protect kidney against IRI-induced AKI, but the underlying molecular mechanism is unclear. In this study, it showed that Oridonin significantly improved kidney damage, and inhibited the expression of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α and MCP-1, as well as macrophage marker F4/80 in kidney and the secretion of inflammatory cytokins in serum of AKI mice in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Increased infiltration of macrophages and CD4 + T cells was also alleviated by oridonin. Consistently, emerging evidence suggest that the beneficial action of oridonin on renal ischemia-reperfusion injury is associated with suppression of macrophage-mediated inflammation [ 10 , 11 ]. It has been also reported that oridonin can modulate the activation and proliferation of T cells to alleviate inflammatory diseases such as inflammatory bowel disease [ 46 , 47 ] and asthma [ 48 ].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Increased infiltration of macrophages and CD4 + T cells was also alleviated by oridonin. Consistently, emerging evidence suggest that the beneficial action of oridonin on renal ischemia-reperfusion injury is associated with suppression of macrophage-mediated inflammation [ 10 , 11 ]. It has been also reported that oridonin can modulate the activation and proliferation of T cells to alleviate inflammatory diseases such as inflammatory bowel disease [ 46 , 47 ] and asthma [ 48 ].…”
Section: Discussionmentioning
confidence: 86%
“…Besides nephrotoxic medications, ischemia-reperfusion injury is also a major cause of AKI [ 24 ]. Recent studies have demonstrated the protective effect of oridonin on renal ischemia-reperfusion injury [ 10 , 11 ]. These findings suggest that the beneficial action of oridonin is not limited to cisplatin-induced AKI but may also be applied to other types of AKI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is mounting evidence that oridonin can inhibit I/R injury, including injury to the myocardium, lower limbs, brain tissue, and kidney, by downregulating oxidative stress and NLRP3-mediated inflammatory pathways [ 9 , 23 , 24 ]. Although these studies have included metabolomics, exosomes, Mincle, and NF-κB, none of the mechanisms have clarified the key role of GSDMD-mediated pyroptosis [ 25 , 26 , 27 ]. In our study, treatment with H/R and oridonin did not alter the expression of GSDMD-FL.…”
Section: Discussionmentioning
confidence: 99%